Implementation Framework Of Green Supply Chain Management In Malaysia Construction Industry - Khoo, Terh Jing (2021)
Construction industry has contributed to the raise of Malaysia’s economic but rapid development has caused environmental issues that severely impacted the daily life of citizens. Therefore, Green Supply Chain Management (GSCM) was introduced to the construction industry in the last decade as this practice has earned good reputation in improving green corporate performances. However, GSCM did not assimilate into majority of the construction activities. This study was intended to identify the main GSCM practices that can be successfully implemented in the construction industry which can improve green corporate performances of property developers significantly and to develop a GSCM framework in construction industry which learned from the manufacturing industry. Since this study was focusing on big area of Malaysia construction industry, a quantitative method was employed to carry out the research with 188 respondents. Moreover, the findings of study revealed that the five main GSCM practices can improve the green corporate performances in the context of environmental, economic and operational performances. Furthermore, the moderation effect of internal and external roles of stakeholders in the supply chain between GSCM implementation and green corporate performances can enhance the impact of GSCM practices on green corporate performances improvement. Therefore, this research has developed a GSCM framework for construction industry successfully as practitioners’ reference. Lastly, future practical implications and conclusions were provided which shed light on GSCM implementation development for property developers in Malaysia construction industry.